RNA-Seq Identification of Cd Responsive Transporters Provides Insights into the Association of Oxidation Resistance and Cd Accumulation in Cucumis sativus L. - Shengjun Feng; Yanghui Shen; Huinan Xu; Junyang Dong; Kexin Chen; Yu Xiang; Xianda Jiang; Chenjie Yao; Tao Lu; Weiwei Huan; Huasen Wang (MDPI AG, 2021)
Greenhouse vegetable production (GVP) has grown rapidly and has become a major force for cucumber production in China. In highly intensive GVP systems, excessive fertilization results in soil acidification, increasing Cd accumulation and oxidative stress damage in vegetables as well as increasing health risk of vegetable consumers. Therefore, enhancing antioxidant capacity and activating the expression level of Cd transporter genes seem to be feasible solutions to promote plant resistance to Cd stress and to reduce accumulated Cd concentration. Here, we used transcriptomics to identify five cucumber transporter genes (CsNRAMP1, CsNRAMP4, CsHMA1, CsZIP1, and CsZIP8) in response to cadmium stress, which were involved in Cd transport activity in yeast. Ionomics, gene expression, and REDOX reaction level association analyses have shown that the transcript of CsNRAMP4 was positively correlated with Cd accumulation and antioxidant capacity of cucumber roots. The expression level of CsHMA1 was negatively correlated with Cd-induced antioxidant capacity. The overexpression of CsHMA1 significantly relieved Cd stress-induced antioxidant activities. In addition, shoots with high CsHMA2 expression remarkably presented Cd bioaccumulation. Grafting experiments confirmed that CsHMA1 contributed to the high antioxidant capacity of cucumber, while CsHMA2 was responsible for the transport of Cd from the roots to the shoots. Our study elucidated a novel regulatory mechanism for Cd transport and oxidative damage removal in horticultural melons and provided a perspective to regulate Cd transport artificially by modulating Cd accumulation and resistance in plants.